Konsep Muraqabah dan Pencapaian Personalitas Kolektif dalam Pemikiran Tasawuf Muhammad Fethullah Gulen - Hakim, Lukman; Saleh, Fauzi; Zaini, Muhammad (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2024)
The basic of Islamic Sufism thought is how to develop human spiritual awareness. In Muhammad Fethullah Gulen's view, Sufism's thought has the urgency of increasing individual spirituality until the collective spiritual personality of Muslims is realized. This collective personality will emerge from the muqarabatullah person, who believes that his life is always under the supervision of Allah. This article discusses the concept of Muraqabah and the formation of a perfect human in the perspective of Muhammad Fethullah Gulen. This study focuses on a literature review that try to describe and analyze the realm of Sufism studies on Muhammad Fethullah Gulen through his works and other writings relevant. Conceptually, Gulen said that Muraqabah is an important element in the study of Sufism which is built on total awareness that humans are always under the supervision of Allah. The predicate of muqarabatullah will be possible to achieve through belief that Allah is always present, looking and seeing in detail our lives, both physically and spiritually. Then put your trust in Allah and open your heart to receive the abundance of divine grace with patience and steadfastness. Gulen stated that achieving this level of faith would make the collective spiritual problems of the Muslim community complete.Abstrak: Dasar utama dari pemikiran tasawuf Islam adalah bagaimana membangkitkan kesadaran spiritual manusia. Dalam pandangan Muhammad Fethullah Gulen, pemikiran tasawuf memiliki urgensitas dalam peningkatan spiritualitas individual hingga terwujud personalitas spiritual kolektif muslim. Personalitas kolektif atau collective personality ini akan muncul dari insan muqarabatullah, yang meyakini bahwa hidupnya selalu dalam pengawasan Allah. Artikel ini membahas tentang konsep muraqabah dan pembentukan manusia paripurna dalam perspektif Muhammad Fethullah Gulen. Kajian ini difokuskan pada kajian kepustakaan yang mencoba mendeskripsikan dan menganalisis ranah kajian tasawuf Muhammad Fethullah Gulen melalui karya dan tulisannya yang relevan. Secara konseptual Gulen menyampaikan bahwa Muraqabah adalah salah satu elemen penting dalam kajian tasawuf yang dibangun atas kesadaran total bahwa manusia selalu dalam pengawasan Allah. Predikat muqarabatullah akan mungkin digapai melalui keyakinan bahwa Allah selalu hadir, memandang dan melihat secara detail kehidupan kita lahir dan batin. Kemudian bertawajuh kepada Allah dan membuka hati menerima limpahan anugerah ilahi dengan penuh kesabaran dan keteguhan. Gulen mengemukakan bahwa pencapaian level keimanan ini akan mewujudkan persoalitas spiritual kolektif komunitas muslim menjadi paripurna.